2020
DOI: 10.1186/s13256-020-02386-w
|View full text |Cite
|
Sign up to set email alerts
|

Catamenial rectal bleeding due to invasive endometriosis: a case report

Abstract: Background: Although gastrointestinal involvement is the most common site for extra-genital endometriosis, deep infiltrative endometriosis, which affects the mucosal layer, is very rare. Case presentation: We present a case of a 41-year-old white woman with cyclic rectal bleeding. Magnetic resonance imaging was done, together with colonoscopy and histologic staining of biopsied samples, which led to the final diagnosis of intestinal invasive endometriosis with recto-sigmoid stricture. Our patient was treated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The fact that endometriosis involves the intestine, whether it occurs in the colorectum or penetrates the muscular layer to reach the mucosal layer, its clinical manifestations are nonspecific and therefore its diagnosis can be very difficult. The lack of etiologic manifestations of intestinal endometriosis makes its differential diagnosis with other diseases challenging 47 and needs to be differentiated from chronic enteritis, ulcerative colitis, Crohn’s disease, appendicitis, isolated rectal ulcer syndrome and especially malignancy, because although they share many clinical symptoms, the treatment approaches are very different. 29 For rectal and sigmoid endometriosis diagnosis can be made by transvaginal ultrasound (TVUS), transrectal ultrasound (TRUS) and, when a rectal mass is present, abdominal CT scan can be used to evaluate rectal endometriosis with variable sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that endometriosis involves the intestine, whether it occurs in the colorectum or penetrates the muscular layer to reach the mucosal layer, its clinical manifestations are nonspecific and therefore its diagnosis can be very difficult. The lack of etiologic manifestations of intestinal endometriosis makes its differential diagnosis with other diseases challenging 47 and needs to be differentiated from chronic enteritis, ulcerative colitis, Crohn’s disease, appendicitis, isolated rectal ulcer syndrome and especially malignancy, because although they share many clinical symptoms, the treatment approaches are very different. 29 For rectal and sigmoid endometriosis diagnosis can be made by transvaginal ultrasound (TVUS), transrectal ultrasound (TRUS) and, when a rectal mass is present, abdominal CT scan can be used to evaluate rectal endometriosis with variable sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic biopsies often obtain tissue that only reflects chronic injury but may lack a basis for a definitive diagnosis of endometriosis lesions, so this may lead to misdiagnosis. 47 Kim et al 54 reported a positive rate of colonoscopic biopsies of only 47.0% (8/17), but their study hypothesized that increasing the number of biopsies may help to improve the positive rate of biopsies. The superficial mucosa of endometriosis lesions has more obvious inflammatory manifestations, and in some cases cryptitis, crypt abscesses and other pathological manifestations similar to inflammatory bowel disease can be seen, 53 thus having an impact on the interpretation of pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, some endoscopic presentations lack specificity, so some physicians choose to perform simultaneous biopsies at endoscopy for suspicious sites. Endoscopic biopsies often obtain tissue that only reflects chronic injury but may lack a basis for a definitive diagnosis of endometriosis lesions, so this may lead to misdiagnosis [47]. Kim et al [54] reported a positive rate of colonoscopic biopsies of only 47.0% (8/17), but their study hypothesized that increasing the number of biopsies may help to improve the positive rate of biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis, defined as functional endometrial tissues growing in other areas outside the uterine cavity and accompanied by debilitating chronic pelvic pain, is estimated to affect about 6–10% of reproductive women [ 1 ]. Rectal endometriosis is one of the uncommon sub-types of deep infiltrating endometriosis that may cause severe clinical symptoms, such as pain, bleeding and obstruction [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%